2022
DOI: 10.21873/cgp.20330
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of CLIC4 Expression in Human Colorectal Cancer Cells for Sensitivity to Growth Inhibition by Fucoxanthinol

Abstract: Background/Aim: Fucoxanthinol (FxOH), a marine carotenoid, induces apoptosis and anoikis in human colorectal cancer (CRC) DLD-1 cells via the down-regulation of chloride intracellular channel 4 (CLIC4) expression, a key molecule for apoptosis. However, whether FxOH is susceptible to CLIC4 expression and its regulatory mechanisms in human CRC cells remains unknown. We investigated the inhibitory effects of FxOH on six types of human CRC cells with CLIC4 regulation. Materials and Methods: The association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…On the other hand, there is an increasing interest in studying fucoxanthinol as it has shown anti-inflammatory, antioxidant, neuroprotective, and antiproliferative activity against different cancer cell lines (colorectal, breast, etc.) [25,44,50]. Li et al [25] found that fucoxanthinol extracted from Nitzschia Laevis exhibited remarkable anti-neuroinflammatory effects.…”
Section: Sargassum Vulgarementioning
confidence: 99%
“…On the other hand, there is an increasing interest in studying fucoxanthinol as it has shown anti-inflammatory, antioxidant, neuroprotective, and antiproliferative activity against different cancer cell lines (colorectal, breast, etc.) [25,44,50]. Li et al [25] found that fucoxanthinol extracted from Nitzschia Laevis exhibited remarkable anti-neuroinflammatory effects.…”
Section: Sargassum Vulgarementioning
confidence: 99%